2022
DOI: 10.2147/jhl.s365526
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style, Work Engagement and Organizational Commitment Among Nurses in Saudi Arabian Hospitals

Abstract: Purpose The purpose of this paper is to examine how nurse managers’ leadership styles, work engagement, and nurses’ organizational commitment are related in Saudi Arabia. Methods This study used a cross-sectional design using an online survey instrument targeted at nurse managers and nurses working in Saudi Arabian hospitals. Multi-factor leadership questionnaire (MLQ), organizational commitment questionnaire (OCQ), and Utrecht Work Engagement Scale (UWES) were used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…Notwithstanding, this study found that nurses weakly agreed that there was sound leadership in terms of collaboration, communication and effective change management within the psychiatric setting. This supports prior studies that demonstrate that junior and senior nurses lacked the level of organization commitment that nurse managers had (Al Dossary, 2022). This lack of commitment by the clinical nursing staff means that implementing cultural change to address issues such as bullying is one of the major concerns when implementing the transformational programme (Al Dossary, 2022).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notwithstanding, this study found that nurses weakly agreed that there was sound leadership in terms of collaboration, communication and effective change management within the psychiatric setting. This supports prior studies that demonstrate that junior and senior nurses lacked the level of organization commitment that nurse managers had (Al Dossary, 2022). This lack of commitment by the clinical nursing staff means that implementing cultural change to address issues such as bullying is one of the major concerns when implementing the transformational programme (Al Dossary, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…This supports prior studies that demonstrate that junior and senior nurses lacked the level of organization commitment that nurse managers had (Al Dossary, 2022). This lack of commitment by the clinical nursing staff means that implementing cultural change to address issues such as bullying is one of the major concerns when implementing the transformational programme (Al Dossary, 2022).…”
Section: Discussionsupporting
confidence: 88%
“… 21 A moderate to strong relationship between “transformational leadership and employee engagement”. Asiri, Mahran, Elseesy 57 Ding, Cao 21 Al-Dossary 58 Transactional leadership Positive correlation with work engagement. Compared to transformational leadership, transactional leadership strongly impacts employee engagement.58 Asiri, Mahran, Elseesy 57 Al-Dossary 58 Servant leadership There is a strong positive effect of servant leadership on work engagement.…”
Section: Resultsmentioning
confidence: 99%
“… Asiri, Mahran, Elseesy 57 Ding, Cao 21 Al-Dossary 58 Transactional leadership Positive correlation with work engagement. Compared to transformational leadership, transactional leadership strongly impacts employee engagement.58 Asiri, Mahran, Elseesy 57 Al-Dossary 58 Servant leadership There is a strong positive effect of servant leadership on work engagement. Qin, Li, Li 59 Ethical leadership Positive relationship with work engagement.…”
Section: Resultsmentioning
confidence: 99%
“…If employees want to show their loyalty by participating in the company's business, HR development is crucial. This attitude makes management's job easier and makes it harder for the company to adapt to new situations 7 .…”
Section: Introductionmentioning
confidence: 99%